1999
DOI: 10.1359/jbmr.1999.14.10.1649
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of CTSK Result in Pycnodysostosis via a Reduction in Cathepsin K Protein

Abstract: Pycnodyostosis, an autosomal recessive osteosclerosing skeletal disorder, has recently been shown to result from mutations in the cathepsin K gene. Cathepsin K, a lysosomal cysteine protease with an abundant expression in osteoclasts, has been implicated in osteoclast-mediated bone resorption and remodeling. DNA sequence analysis of the cathepsin K gene in a nonconsanguineous family demonstrated compound heterozygozity for mutations in two affected siblings. We have identified a missense mutation with a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 14 publications
1
28
1
1
Order By: Relevance
“…The morphology and abundance of TRAP-positive active osteoclasts seen in the alveolar bone surface around the tooth germ of CK-/ -mice were similar to those of the wild-type mice. The findings are not consistent with the previous finding that pycnodysostosis patients having mutation of the CK gene display abnormal craniofacial development and delayed eruption of dentition (14,33). Although long bones of CK-/ -mice revealed impaired bone resorption and closely resemble those described for pycnodysostosis patients, it has been reported that no overt phenotypic abnormalities were observed until the age of 10 months (16).…”
Section: Discussioncontrasting
confidence: 96%
“…The morphology and abundance of TRAP-positive active osteoclasts seen in the alveolar bone surface around the tooth germ of CK-/ -mice were similar to those of the wild-type mice. The findings are not consistent with the previous finding that pycnodysostosis patients having mutation of the CK gene display abnormal craniofacial development and delayed eruption of dentition (14,33). Although long bones of CK-/ -mice revealed impaired bone resorption and closely resemble those described for pycnodysostosis patients, it has been reported that no overt phenotypic abnormalities were observed until the age of 10 months (16).…”
Section: Discussioncontrasting
confidence: 96%
“…The second explanation would suggest the non-core haplotype chromosome in II:2 is much more distantly related than the other seven core-haplotype chromosomes. Our results confirm the disease locus previously reported [6][7][8][9][10][11] and show that at least three mutations exist in the Danish population. Consequently, this study indicates locus homogeneity and allele heterogeneity in pycnodysostosis within an outbred population.…”
Section: Discussionsupporting
confidence: 92%
“…8,9 Another seven mutations were described in nine unrelated families. 10,11 To focus on the question of locus heterogeneity and allele heterogeneity within the same population we here present a study of mutations and haplotypes in eight patients from five independent families with pycnodysostosis in an outbred Caucasian population.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Genetic linkage analysis of two kindreds assigned the locus for pycnodysostosis to chromosome 1q21, and missense, nonsense, and stop mutations involving the cathepsin K gene were found subsequently to cosegregate with the disease. (3)(4)(5) Cathepsin K is a lysosomal cysteine protease highly expressed in osteoclasts alone, thereby restricting the phenotype of pycnodysostosis to bone. (6) The treatment of pycnodysostosis is restricted to symptomatic management of fractures and other skeletal problems, but insights provided by identification of underlying gene mutations have led to the development of cathepsin K inhibitors for the treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%